2011
DOI: 10.1002/chem.201100067
|View full text |Cite
|
Sign up to set email alerts
|

Furan‐Oxidation‐Triggered Inducible DNA Cross‐Linking: Acyclic Versus Cyclic Furan‐Containing Building Blocks—On the Benefit of Restoring the Cyclic Sugar Backbone

Abstract: Oligodeoxynucleotides incorporating a reactive functionality can cause irreversible cross-linking to the target sequence and have been widely studied for their potential in inhibition of gene expression or development of diagnostic probes for gene analysis. Reactive oligonucleotides further show potential in a supramolecular context for the construction of nanometer-sized DNA-based objects. Inspired by the cytochrome P450 catalyzed transformation of furan into a reactive enal species, we recently introduced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
0
28
1
Order By: Relevance
“…Similarly, dG does not form ICLs with dioxobutane, or the bis-electrophile derived from furan oxidation, which are also 1,4-dicarbonyl molecules. 5,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, dG does not form ICLs with dioxobutane, or the bis-electrophile derived from furan oxidation, which are also 1,4-dicarbonyl molecules. 5,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…While the cross-linking reaction itself is straight-forward, the vinyl-substituted nucleosides need to be chemically synthesized and subsequently converted into their phosphoamidites for chemical DNA synthesis. The same holds true for cross-links based on aldehyde [ 8 , 35 37 ] or click chemistry [ 38 ]. In addition, long linkers that might interfere with protein binding are typically employed.…”
Section: Introductionmentioning
confidence: 88%
“…The 4-oxo-enal moieties generated through oxidation of furan ring have been previously reported 13 21 22 23 for ICL formation between the exocyclic amine of adenine or cytosine and the aldehyde group of 4-oxo-enal moiety 13 21 22 23 . Different from previous 4-oxo-enal moieties that contain two carbonyl groups, we developed a 4-oxo-enal moiety with one carbonyl and one amide groups.…”
mentioning
confidence: 98%
“…More promising results are achieved when a reactive cross-linking moiety is produced from a stable precursor, e.g. disulfide bonds 3 , quinone methides 6 11 14 , carbazoles 5 15 16 , benzophenone derivatives 17 , phenylselenyl derivatives of pyrimidines 18 , abasic site 19 20 , and furan derivatives 13 21 22 23 . Among them, Madder reported that methylene blue-induced 1 O 2 formation triggered furan oxidation for further DNA cross-linking 13 21 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation